Functional changes of neural circuits in stroke patients with dysphagia: A meta‐analysis. Issue 3 (24th May 2017) - Liu, Lu; Xiao, Yuan; Zhang, Wenjing; Yao, Li; Gao, Xin; Chandan, Shah; Lui, Su
Abstract: Objective: Dysphagia is a common problem in stroke patients with unclear pathogenesis. Several recent functional magnetic resonance imaging (fMRI) studies had been carried out to explore the cerebral functional changes in dysphagic stroke patients. The aim of this study was to analysis these imaging findings using a meta‐analysis. Methods: We used seed‐based d mapping (SDM) to conduct a meta‐analysis for dysphagic stroke patients prior to any kind of special treatment for dysphagia. A systematic search was conducted for the relevant studies. SDM meta‐analysis method was used to examine regions of increased and decreased functional activation between dysphagic stroke patients and healthy controls. Results: Finally, six studies including 81 stroke patients with dysphagia and 78 healthy controls met the inclusion standards. When compared with healthy controls, stroke patients with dysphagia showed hyperactivation in left cingulate gyrus, left precentral gyrus and right posterior cingulate gyrus, and hypoactivation in right cuneus and left middle frontal gyrus. Conclusions: The hyperactivity of precentral gyrus is crucial in stroke patients with dysphagia and may be associated with the severity of stroke. Besides the motor areas, the default‐mode network regions (DMN) and affective network regions (AN) circuits are also involved in dysphagia after stroke.